A true home - George, K. (Kallie), 1983- (George, K. (Kallie), 1983- Heartwood Hotel, 2017)
Mona the mouse is precisely the maid they need at the grandest hotel in Fernwood Forest, where animals come from far and wide for safety, luxury, and comfort.